2002
DOI: 10.1515/zna-2002-6-709
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of 2H Nuclear Quadrupole Interaction in Very Short Hydrogen Bonds in Some Organic Acidic Salt Crystals

Abstract: The 2 H nuclear quadrupole interaction parameters, 2 and , are closely related to the shape of the potential energy surface at hydrogen bonds and depend sensitively on their geometry. We measured the temperature dependence of the 2 H NMR spectra of the crystalline acidic salts KDCO 3 , KD acetylenedicarboxylate, RbD acetylenedicarboxylate, and KD maleate, which contain very short O-D O type hydrogen bonds. The temperature coefficient decreases with increase in the O O distance in the hydrogen bond. Ab inito mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 15 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…21 For NMA, however, a 6.9 kHz increase was observed when the temperature increased from 200 to 300 K. 44 Similar unusual temperature dependence of quadrupolar couplings has also been reported for other systems with short hydrogen bonds. 45,46 Previous ab initio calculations, even with high-level corrections for electron correlation, did not accurately reproduce such NMR data observed in such strongly hydrogen-bonded systems. 47,48 It has been shown that a simple model based on the anharmonicity of the hydrogen bond potential fails to describe temperature dependence of quadrupolar couplings.…”
Section: ■ Introductionmentioning
confidence: 99%
“…21 For NMA, however, a 6.9 kHz increase was observed when the temperature increased from 200 to 300 K. 44 Similar unusual temperature dependence of quadrupolar couplings has also been reported for other systems with short hydrogen bonds. 45,46 Previous ab initio calculations, even with high-level corrections for electron correlation, did not accurately reproduce such NMR data observed in such strongly hydrogen-bonded systems. 47,48 It has been shown that a simple model based on the anharmonicity of the hydrogen bond potential fails to describe temperature dependence of quadrupolar couplings.…”
Section: ■ Introductionmentioning
confidence: 99%